Verification of Business Actor's Statement for Halal Certification of Micro Enterprises in Sidoarjo Regency, East Java - Hana Catur Wahyuni; Puspita Handayani; Ima Faizah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Micro and small businesses have an important role in the economic structure in Indonesia so that the products produced need to be increased in selling value and competitiveness. One method to increase it is halal certification. This is necessary to provide guarantees of product halalness to consumers amid the risks that threaten to change the status of halal to non-halal. To facilitate the halal certification process so as to encourage more micro and small businesses to obtain halal certificates, the Government facilitates the submission of halal certification based on the statements of business actors as stated in the Decree of the Head of the Halal Product Assurance Agency No. 33 of 2022. This community service aims at to carry out halal verification by the halal product process assistant (pph) who has been registered by the Halal Product Assurance Administration Agency (BPJPH). The verification process was carried out on 4 (four) micro and small business actors in the Sidoarjo Regency, East Java. Verification by the PPH assistant is carried out online through the ptsp.halal.go.id system. The verification stage by the PPH assistant is carried out in 3 (three) stages, namely the administrative verification stage, field verification and verification. The results of the verification activities in the 3 (three) stages indicate that micro and small business actors have met the requirements in applying for halal certification and obtained STTD (Document Receipt Letter).